Development of task-based language teaching in virtual reality: A case study - Ogawa, Koyo (Technology in Language Teaching & Learning, 2025)
Virtual reality (VR) has attracted increasing interest for its potential to enhance second language acquisition through immersive and interactive experiences. However, effectively integrating VR with established language teaching pedagogy remains a critical challenge. This study addresses that gap by embedding the principles of task-based language teaching (TBLT) into a custom-designed VR learning environment. Using “making orders in a bar” as a representative target task, the study illustrates the design of pedagogical tasks and the development of an original VR environment using open-source tools. Employing a small-scale case study design, the research investigates whether this VR-based TBLT (VR-TBLT) facilitates learners’ acquisition of the target discourse and supports the transfer of skills to real-world contexts. It also explores learners’ perceptions of the VR-TBLT experience. The findings indicate that the VR-TBLT approach promotes the use of the target language, supports near transfer to real-world tasks through contextual similarity, and enhances learners’ engagement. Participants reported high levels of enjoyment and presence within the VR environment, although minor technological issues were noted. These results underscore VR-TBLT’s potential as a pedagogically grounded tool for language learning and highlight key considerations for future research on scalability and long-term outcomes.